Fragmented Scaffolding in Arabic Textbooks: A Genre-Based Analysis of the Teaching Learning Cycle in Indonesian Madrasah Education - Safira Nur Rizqina; Shofa Musthofa Khalid (Universitas Islam Negeri Madura, 2026)
This study investigates the implementation of the Teaching Learning Cycle (TLC) in the Grade XI Arabic textbook published by KSKK Madrasah (2020). Using qualitative content analysis grounded in Systemic Functional Linguistics and Genre-Based Approach, the study analyzed six textbook chapters through the stages of BKOF, MOT, JCOT, and ICOT. AI-assisted comparative validation using ChatGPT-5 was additionally employed to support analytical consistency between manual and AI categorization results. The findings reveal that although all TLC stages formally appeared in the textbook, their pedagogical continuity was implemented inconsistently. BKOF and MOT generally provided adequate contextual and rhetorical support, while JCOT frequently lacked collaborative text construction and was often reduced to oral interaction. Consequently, several ICOT activities required students to produce independent texts without sufficient scaffolding. The study contributes to genre-based Arabic textbook evaluation within the context of Indonesian madrasah education.